Evaluating Digital Citizen Engagement : A Practical Guide - World Bank Group (World Bank, Washington, DC, 2016)
With growing demand for transparency, accountability and citizen participation in policy making and service provision, engagement between citizens and their governments, as well as with donors and the private sector that deliver government services, is increasingly important. Increased use of technology brings both opportunities and challenges to citizen engagement processes, including opportunities for collecting, analyzing and evaluating data about these processes. This guide provides practical steps to assess the extent to which digital tools have contributed to citizen engagement and the help to understand the impact that the introduction of technology has had on the engagement processes. With examples and lessons from case studies from Brazil, Uganda, Cameroon and Kenya, the guide provides practical tools and guidelines for use in evaluating the expanding field of digital citizen engagement.